The influence of stand structure on abundance and moisture content of fuel in the Cilegon PLTGU Conservation Area - Saharjo, Bambang Hero; Hutauruk, Cristian Santo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Stand structure will affect fuel characteristics in forest stands. Forest fuel characteristics have an important role in determining fire behavior in forest fires. The purpose of this study was to determine the effect of vegetation stand structure on the abundance and moisture content of fuels that affect the chances of forest fires in the Cilegon PLTGU conservation area. Vegetation analysis and measurement of fuel characteristics were conducted in two different stands, namely monoculture and polyculture stand. The parameters used to conduct vegetation analysis are tree height, first branch height, Diameter at Breast Height (DBH) and crown cover, while the parameters of fuel characteristics are abundance, thickness and moisture content of fuel. Based on the results of fuel characteristics research in monoculture stands resulted in abundance, thickness and moisture content of fuel respectively 11.35 tons/ha, 15 cm and 13,61%, while in polyculture stands resulted in abundance, thickness, and moisture content of fuel respectively 14.57 tons/ha, 10 cm and 16,46%. The moisture content in monoculture and polyculture stands is below the percentage value of 30% so that the two stands in the Cilegon PLTGU conservation area include areas that are still prone to forest fires. Keywords: forest fires, fuel, moisture content, stand structure